IV. ON A RAZOR'S EDGE 1844-7850 (A History of Victoria University, 1952)
Acute exercise markedly alters blood glucose levels and the secretion of glucose-regulating hormones. However, as a central organ involved in glucose homeostasis, the molecular mechanisms underlying pancreatic responses to acute exercise remain poorly understood. Therefore, this study aimed to investigate the molecular adaptations of pancreatic tissue to acute exercise using a mouse treadmill exercise model combined with integrated multi-omics analyses. C57BL/6 mice were randomly assigned to either an exercise group or a control group, and pancreatic tissues were collected immediately after exercise intervention for transcriptomic and metabolomic analyses. Acute exercise significantly increased blood glucose and glucagon levels while reducing circulating insulin levels. Metabolomic analysis revealed significant elevations in several metabolites related to amino acid metabolism, including tryptophan, kynurenic acid, leucine, isoleucine, and valine. Transcriptomic analysis further identified significant upregulation of multiple genes, including Ins1, Ins2, Cdkn1a, Dusp1, Fkbp5, and Pdk4. These findings suggest that acute exercise induces rapid transcriptional and metabolic remodeling in pancreatic tissue and that these differential metabolites and genes may contribute to the pancreatic adaptive response to acute exercise.